Relative positioning control of flexible structure for precise positioning stage - Hironori OGAWA (The Japan Society of Mechanical Engineers, 2020)
Precise positioning technologies are widely used in industrial machines such as device manufacturing equipment. Many studies have been done on feedback control systems for precise positioning stages that improve accuracy by using sensor signal feedback. However, the sensor output does not always directly indicate the performance of the industrial machines because the final requirement of a stage system is generally to adjust a movable stage to a target structure. Therefore, the relative displacement between the stage and the target structure must be controlled. However, the stage and other structures must be considered as elastic elements, especially for precise positioning devices. Thus, this study aims to achieve precise positioning in relative displacement between flexible structures. The authors previously proposed a relative displacement observer that estimated the relative displacement between the stage and the target structure by using only the stage displacement. In this paper, we propose additional control system for relative displacement by using self resonance cancellation technique. The positioning performance of the proposed system is evaluated in numerical simulation and experimental stage system. Results of numerical simulation and experiments show that the proposed control system improves the relative positioning performance.